Case report: Diagnosis and treatment of a chinchilla's old radius and ulna fracture - Siyu Long; YuJing Qiao; Hua Cao; Tiantian Qiu; Yuji Chen; Yaoqin Shen (BMC, 2023)
Abstract The cortex of the limb bones of chinchillas is very thin and brittle, so it is prone to fractures of the limb bones, among which fractures of the tibia, radius and ulna are the most frequent types. When a chinchilla has a closed fracture, it can be immobilized with a splint, cast, or bandage. If the broken end of the fracture pierces the skin, it is best to choose internal fixation or external fixation brackets for treatment. In this report, a 0.661 kg, 2-year-old male uncastrated chinchilla was presented to the Veterinary Teaching Hospital of Huazhong Agricultural University due to an old fracture of the right forearm. With the consent of the owner, we decided to use a 25-gauge needle as an IM pin to fix the fracture. Ten days after surgery, the wound had healed well, and the limb could support body weight, but the palm did not show a grasping position. Twenty four days after the operation, the affected limb had not regained the ability to grasp. The X-ray showed a slight rotation of the IM pin and good callus growth in the ulna, but not in the radius. One month after the operation, it was found that the function of the affected limb of the chinchilla was normal and the grasping ability was restored through follow-up consultation and the return visit.